Pengaruh Digital Marketing, Direct Marketing dan Brand Image terhadap Minat Mahasiswa Baru Universitas PGRI Semarang - Muhamad Abidin; Ika Indriasari; Rr. Hawik Ervina Indiworo (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
The number of high school graduates continues to increase every year, followed by the growth in the number of universities that trigger competition in attracting new students, including Universitas PGRI Semarang. To face this competition, universities utilize digital marketing, direct marketing, and brand image as promotional strategies. This study aims to analyze the influence of these three variables on the interest of new students at Universitas PGRI Semarang. The method used is quantitative descriptive with a sample of 100 new students in the 2024/2025 academic year, using a purposive sampling technique. Data analysis includes validity, reliability, normality, multicollinearity, heteroscedasticity tests, as well as T, F, and coefficient of determination (R²) tests. The results of the study indicate that digital marketing, direct marketing, and brand image have a positive effect on student interest, with digital marketing as the most dominant factor.